If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7 + -7x = 197 + -42x Solving 7 + -7x = 197 + -42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42x' to each side of the equation. 7 + -7x + 42x = 197 + -42x + 42x Combine like terms: -7x + 42x = 35x 7 + 35x = 197 + -42x + 42x Combine like terms: -42x + 42x = 0 7 + 35x = 197 + 0 7 + 35x = 197 Add '-7' to each side of the equation. 7 + -7 + 35x = 197 + -7 Combine like terms: 7 + -7 = 0 0 + 35x = 197 + -7 35x = 197 + -7 Combine like terms: 197 + -7 = 190 35x = 190 Divide each side by '35'. x = 5.428571429 Simplifying x = 5.428571429
| 4a+3a= | | -82-10x=10x+18 | | 4x+14=-41-7x | | 12-2x=2+3x | | 6m+11=83 | | -2-5=13-10x | | 3m+3n+2p+4r= | | 6x+30=0 | | 4x-4=12x-68 | | 7j+11jk+k+9= | | 6x+37=15x-62 | | 16n=8(2n-10) | | 4m+3+m+1= | | 6(2y+3)-4(y-5)=0 | | 4x+4y+4z+4= | | 2x+10=64 | | 3c+4d+5c+8= | | 3a+2+3a+7= | | 2(4+3r)=3(r+1)+11 | | 5x=x+10 | | 4(2y+5)=3(5y-2) | | 8+2x-3=25 | | 4a-6-2(a-1)= | | 5a-2-3a+7= | | -2a+3a+6= | | 6q-9=12+3q | | -3(m-1)+4m+2= | | 4=x^2-7 | | 7x+4-5x-8= | | 5x-4=2(x-2) | | 2x+16y+13=0 | | 22y+8=23y-4 |